2003
DOI: 10.1097/01.mp.0000097366.88165.08
|View full text |Cite
|
Sign up to set email alerts
|

Dedifferentiated Adenoid Cystic Carcinoma: A Clinicopathologic Study of 6 Cases

Abstract: Dedifferentiated adenoid cystic carcinomas are a recently defined, rare variant of adenoid cystic carcinomas characterized histologically by two components: conventional low-grade adenoid cystic carcinoma and high-grade "dedifferentiated" carcinoma. We examined six cases and analyzed their clinicopathologic profiles, including immunohistochemical features and p53 gene alterations. The 6 patients (3 men and 3 women) had a mean age of 46.8 years (range, 34-70 y). The mean size of the tumors was 3.5 cm (range, 1.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
138
2
1

Year Published

2009
2009
2017
2017

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 129 publications
(149 citation statements)
references
References 33 publications
8
138
2
1
Order By: Relevance
“…Using a cutoff of 5 % or higher, there was no statistically significant difference in outcome for those with a high proliferation index versus those with a low proliferation index: mean 8.2 versus 10.5 years, respectively; and 64.3 versus 53.6 % dead of disease, respectively. This is different from others who have reported a statistically significant difference [76,77,105]. However, an increased ki-67 index is noted in pleomorphic adenoma that undergo malignant transformation to ACC ex-pleomorphic adenoma [105,145,146].…”
Section: Immunohistochemical Studiescontrasting
confidence: 92%
See 1 more Smart Citation
“…Using a cutoff of 5 % or higher, there was no statistically significant difference in outcome for those with a high proliferation index versus those with a low proliferation index: mean 8.2 versus 10.5 years, respectively; and 64.3 versus 53.6 % dead of disease, respectively. This is different from others who have reported a statistically significant difference [76,77,105]. However, an increased ki-67 index is noted in pleomorphic adenoma that undergo malignant transformation to ACC ex-pleomorphic adenoma [105,145,146].…”
Section: Immunohistochemical Studiescontrasting
confidence: 92%
“…It is important to note that recurrences often developed soon after resection, but late recurrences can be seen up to 14.8 years after initial presentation. When distant metastases are present, lung, liver, and bone are the most common sites, followed by brain, kidney, skin and soft tissues [10,57,65,76,99,121,153].…”
Section: Prognosismentioning
confidence: 99%
“…The de-differentiation of ACC to more aggressive types in salivary gland tumors was first reported by Cheuk et al [7] in 1999. Nagao et al [8] and Ide et al [9] also reported similar cases for ACC located outside the breast.…”
Section: Discussionmentioning
confidence: 63%
“…The existence of a de-differentiated component of higher malignancy grade worsens the prognosis [7,8]. However, the exact magnitude of this is difficult to estimate because of the limited number of cases described in the literature and the wide diversity of the de-differentiation patterns.…”
Section: Discussionmentioning
confidence: 99%
“…That this grading scheme does indeed reflect a form of tumor progression is supported by cases where ACC tumors have displayed increasing solid growth and histologic atypia during the course of tumor recurrence, with increasingly aggressive clinical behavior [17]. ACC may also rarely undergo dedifferentiation, with a high grade anaplastic carcinoma component arising in a conventional ACC [18][19][20]. High-grade transformation is characterized by irregular, jagged infiltrating islands of tumor cells or large confluent areas of solid growth, and the background stroma displays a fibrocellular desmoplasic change, which is typically not seen in conventional ACC.…”
Section: Introductionmentioning
confidence: 99%